ETHNICISM AND RELIGION IN CONFLICT - Iroegbu, Pantaleon (Journal of Dharma, 1997)
A well-ordered society does not presuppose a homogeneity of people and culture; the structure of political life is a product of the variety of societal elements that need to be organized. These elements include language, religion, ethnic group or tribe, as well as varying social strata, the economy, differentiations in human and natural resources, the presence of interest-groups, and many other factors that distinguish family, regional, and cultural groups. Heterogeneity makes government imperative. At the same time, these very heterogeneous elements make governmental functioning difficult.